The Effect Of Soft Skill On Work Readiness Facing Society 5.0 In Informatics Engineering Students Of STMIK Pelita Nusantara Medan - Risa Kartika Lubis (Junal Ilmu Manajemen, 2021)
The dynamic world of work conditions is influenced by various economic factors, technology and market demand. Higher education is a sub system that prepares graduates to enter the world of work, because of that, universities must pay attention to the content of soft skills attributes in the learning process from an early age. Without it, universities will only produce academically intelligent graduates who are easy to find work but do not survive in the world of work. This research is a study on the influence of soft skills on the work readiness of final semester management students of STMIK Pelita Nusantara. The respondents used were 100 students with accidental sampling technique using a questionnaire. Sample testing is done by simple regression test and the results obtained show that there is a significant influence between soft skills and student work readiness.